A 3D BEM/FEM formulation for the static analysis of piled rafts and capped pile groups subjected to vertical and horizontal loads. (June 2019) - Luamba, Endi Samba; Paiva, João Batista de
Abstract: In this paper, soil-structure interaction problems are analysed using a three-dimensional formulation obtained by combining the Boundary Element Method (BEM) and the Finite Element Method (FEM). Structural elements that interact with the soil are modelled with the FEM. Soil, which is considered as a semi-infinite, homogeneous, linear elastic and isotropic medium, is modelled with the BEM using Mindlin's fundamental solution. A pile is discretized by several three-dimensional finite beam elements. A plate is discretized by finite flat shell elements, making it possible to consider the bending and membrane effects. The vertical and horizontal loads in the plate-pile-soil system are directly applied to the plate. This approach allows for a static analysis of the full interaction between capped pile groups or piled rafts and the soil. The developed formulations can also be extended to dynamic or non-linear analyses. Coupling between the BEM and FEM is performed through a mixed formulation in which the matrix of the soil's influence coefficients obtained by BEM is added to the stiffness matrix of the structural elements obtained by FEM, resulting in an equivalent stiffness matrix. Numerical examples of the plate-pile-soil interactions are solved, and their results are compared with those of other formulations.